The information set of the Fed's policy reaction function. (30th August 2019) - Laopodis, Nikiforos T.
This paper examines the Federal Reserve's information set in setting monetary policy. A number of macroeconomic variables are examined during the regimes of Volcker, Greenspan, Bernanke, and Yellen. The empirical findings from the Fed's benchmark reaction function indicate that there have been distinct reactions of stock returns to fed funds rate shocks during each different monetary regime. These reactions appear more turbulent and persistent during the Bernanke and Yellen regimes than during the previous Chairs's terms. When augmenting the Fed's reaction function with variables such as credit and term spreads, the unemployment rate, and financial uncertainty, it was revealed that the Fed might have actually considered each of these magnitudes separately in its deliberations to conduct monetary policy. Finally, stock returns were found to react differently over different phases of the business cycle, following movements in the Fed's reaction function, with their reactions additionally found to be dissimilar during each bull and bear stock markets.